The dynamic effects of monetary policy shocks on manufacturing sector growth in Nigeria - Amusa, Rasheedat Gbeminiyi Omotola (My University, 2022)
Over the years there have been a series of monetary interventions taken by the monetary authorities in Nigeria to influence the growth of the manufacturing sector. These monetary interventions are usually called monetary policy shocks. The manufacturing sector remains an important sector of the Nigerian economy where the country is hoping to diversify reducing its dependence of the country on oil. This study investigated the effects of monetary policy shocks on manufacturing sector growth in the Nigerian economy from 1980Q1 to 2019Q4. The study was carried out under two broad modular theses namely examining the effects of monetary policy shocks on the manufacturing output growth of the Nigerian manufacturing sector and investigating the transmission mechanism through which global shocks transmit to the manufacturing output. The achievement of the first objective was done using the cointegration and Vector Error Correction Model where the long and short-run effects of monetary policy variables and other macroeconomic variables on the output of the manufacturing sector were examined. The second aspect of objective one which investigates the impact of monetary policy shocks on manufacturing output as well as the transmission mechanism through which the global shocks transmit to the manufacturing output growth was done using the VECM/VAR method with the application of both impulse response function and variance decomposition. Data on the variables were sought from both the World Bank tables and the International Financial Statistics 2020 edition. The result obtained from the first aspect of the analysis showed that there exists a long-run relationship between manufacturing output growth and monetary policy variables such as interest rate and money supply and other macroeconomic variables. Furthermore, the result further confirms the significant impact of the monetary policy rate on the manufacturing output growth both in the long and short run. Money supply failed to show the same significant impact. Notwithstanding, external variables such as World Oil Price and Federal Fund Rate also showed a significant effect on manufacturing output. Other variables with a long-run significant impact on manufacturing output growth are the Inflation rate and exchange rate. capita and labour. The second objective of the study which investigated the transmission mechanism through which global shocks affect the manufacturing output is done using the impulse response function and variance decomposition tools of the VECM. The confirmation of cointegration showed the adoption of VECM as against VAR and the impulse response function vividly showed the responses of manufacturing output to both the monetary policy shocks and global shocks as well as the medium through which these shocks are transmitted. The results further indicated that the effect of global shocks on manufacturing output makes use of the exchange rate channel and interest rate channel directly. Further analysis shows that exchange rate shocks also affect manufacturing output directly or indirectly through inflation rate. Again, Monetary policy shocks affect manufacturing output directly or indirectly through inflation and private sector credit respectively. The study recommends a more purposeful effort on the part of the monetary authorities in Nigeria to minimize the effect of external shocks on the manufacturing sector which has been aggravating the negative effects of monetary policy shocks on manufacturing output and frustrating internal monetary policy efforts of the Central Bank of Nigeria.
Thesis (Ph.D. (Economics)) -- University of Limpopo, 2022
Keywords: Monetary policy; Manufacturing sector; Nigerain economy; Monetary policy shocks; Monetary policy; Financial crises -- Effect of monetary policy on; Nigeria; Nigeria -- Economic conditions; Monetary policy -- Nigeria